COMPARATIVE STUDY ON THE CONDITIONS FOR THE MANIFESTATION OF LOCAL AUTONOMY IN THE CASE OF ADMINISTRATIVE SYSTEMS IN THE FRENCH COMMUNE OF MÉRIGNAC, THE CANADIAN PROVINCE OF QUEBEC AND THE ROMANIAN COMMUNE OF TUDORA - Petronela SCUTARIU; Andreea DOROFTEI (USV Annals of Economics and Public Administration, 2022)
The present research aims at the comparative analysis of the conditions that support the manifestation of the principle of autonomy in public administration in the administrative-territorial units, with particularization at the commune of Mérignac in France, Quebec province in Canada and Tudora commune in Romania. Through the approach, we found that, in support of local autonomy, the French territorial communities are communes, departments, regions, communities with special status, overseas communities; the Canadian territory is divided into provinces and territories, the province of Quebec being divided by municipalities, cities, parishes, villages, cantons, united cantons; the Romanian national community is divided into local communities formed into counties, municipalities, cities and communes. At the level of the three administrative-territorial units analyzed, human, material and financial public resources were identified, which together provide support for the applicability of the principle of autonomy. In addition, the consistency of local autonomy is also conferred by the recognition of the full competence of the local public administration authorities to manage the affairs of the administrative-territorial units. The fact that the acts of the local public administration authorities in the three territorial divisions are subject to control does not express a restriction on the principle of autonomy.